شرح آلية تأثير تقنية البلوك تشين على التجارة الدولية هل يمكن لتقنية البلوك تشين أن تُحدث ثورة في التجارة الدولية؟ - بوصبيع صالح، رحيمة; جامع ، عبد الله (University Of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة لشرح الية عمل تقنية (Blockchain) في التجارة الدولية وتقديم المزايا المحتملة لاستخدامها، معتمدين في ذلك على المنهج الوصفي، والمنهج التحليلي، وبيانات إحصائية حول هذه التقنية وما يمكن ان تقدمه للاقتصاد العالمي والتجارة الدولية. وقد خلصت الدراسة إلى ان تقنية البلوك تشين رغم حداثتها الا انها أظهرت إمكانات كبيرة في تمويل التجارة الدولية وتتبع عملياتها ومراحلها، اذ انعكس الدور على الرفع من مستوى الثقة والامان والشفافية والسرعة وتخفيض تكاليف المعاملات الرقمية والإسهام في الحفاظ على معلومات المتعاملين، ولا يزال المجال مفتوحا لتطبيق هذه التكنولوجيا والتوسع فيهAbstract: This study aims to explain the operational mechanism of blockchain technology in international trade and to present its potential advantages, relying on both the descriptive and analytical methodologies, as well as statistical data concerning this technology and what it can offer to the global economy and international trade. The study concluded that although blockchain technology is relatively new, it has demonstrated significant potential in financing international trade and tracking its operations and stages. Its role has been reflected in raising the levels of trust, security, transparency, and speed, reducing the costs of digital transactions, and contributing to the preservation of the information of the involved parties. Furthermore, the field remains open for the application and expansion of this technology.
Explanation of the Mechanism by which Blockchain Technology Impacts International Trade Can blockchain revolutionize international trade?
مداخلة
Keywords: البلوك تشين; العقود الذكية; التجارة الدولية